3D multi-source CSEM simulations: Feasibility and comparison of parallel direct solvers - Puzyrev, Vladimir; Koric, S. (2015)
Modern numerical algorithms for computational electromagnetics lead to many large sparse systems of linear equations. Their solution takes up to 90% of the total computational time in the geophysical inversion process. This paper provides evaluation and comparison of several state-of-the-art direct solvers in a massively parallel environment. We determine the largest complex systems that can be solved today with these methods and evaluate their performance and scalability on one of the world's most powerful supercomputers. Small sensitivity of direct methods to the number of sources, modeling frequency and conductivity distribution in the subsurface is confirmed. The results show the potentials and limitations of different parallel implementations on a petascale high-performance computing system.